Peran Pendidikan Agama Dalam Membimbing Remaja Kristen Universitas Negeri Medan Untuk Menghadapi Pergaulan Bebas - Mangido Nainggolan; Angely Agriani br. Siahaan; Catherina Teresia Siburian; Dino Aldo Dermawan Pardosi; Julika Indriani Manik; Kristina Natalia Hutagalung; Maya Febrina Sinaga; Nadia Rouli Sinaga; Udur Astiona Sitanggang; Wiwik Romauli Br Nababan (Journal on Education, 2024)
Advances in technology and easy access to social media have influenced adolescent association. They are exposed to a variety of content that is often contrary to religious values. This causes a greater challenge in providing a strong understanding of religion to teenagers. This method is a qualitative method will provide a deep understanding of the experiences and perspectives of adolescents, as well as provide insight into how religious education can play an important role in guiding them to conduct interviews and observations. Based on the results of religious education research has a crucial role in guiding adolescents to deal with promiscuity. Through understanding of moral values, ethics, social responsibility, and spiritual values, adolescents can make wise, responsible, and positive decisions in their lives